A bonding evolution theory study of the mechanism of [3+2] cycloaddition reactions of nitrones with electron-deficient ethylenes1. Issue 72 (6th August 2015) - Ríos-Gutiérrez, Mar; Pérez, Patricia; Domingo, Luis R.
<x xml:space="preserve">Abstract</x> BET study of the mechanism of zw-type [3+2] cycloaddition reactions of nitrones with electron-deficient ethylenes.